Trends in Islamic Psychotherapy for Enhancing Spiritual Well-Being in Drug Addiction Recovery - Mukti, Defiana; Handayani, Satriana (Indonesian Journal of Islamic Counseling, 2024)
This article explores the effectiveness of Islamic psychotherapy in enhancing spiritual well-being during drug addiction recovery in Indonesia. The research uses a qualitative method with a case study design, and data analysis is based on in-depth interviews, observations, and surveys. The findings show that Islamic psychotherapy significantly reduces stress, improves interpersonal relationships, and increases social support from the community, all of which contribute to the success of patient recovery. Data reveal a decrease in average stress scores from 78 to 42 and an improvement in interpersonal relationships from 55 to 81 after therapy. Community support has been shown to expedite the recovery process, with 75% of patients reporting significant benefits. These findings support the integration of spiritual practices into addiction therapy and offer a new perspective that addresses the limitations of conventional methods. The study concludes that an approach combining spiritual aspects and social support provides a more holistic and effective solution for drug addiction rehabilitation.